Mycobactin analogue interacting with siderophore efflux-pump protein: insights from molecular dynamics simulations and whole-cell assays - Shyam, Mousumi; Thakur, Abhishek; Velez, Caroline; Daniel, Chris; Acevedo, Orlando; Bhakta, Sanjib; Jayaprakash, Venkatesan (Frontiers in Antibiotics, 2024)
Introduction In response to continued public health emergency of antimicrobial resistance (AMR), a significant key strategy is the discovery of novel mycobacterial efflux-pump inhibitors (EPIs) as potential adjuvants in combination drug therapy. Interest in identifying new chemotypes which could potentially synergize with the existing antibiotics and can be deployed as part of a combination therapy. This strategy could delay the emergence of resistance to existing antibiotics and increase their efficacy against resistant strains of mycobacterial species. In recent decades, notable approaches have been accounted for EPI development and have resulted in the discovery of several EPIs including SQ109 and AU1235. In context, to accelerate newer EPIs with novel mode of action here we have discussed mycobactin analogues and highlighted in silico binding orientation with siderophore efflux-pump proteins MmpL4/5. Methods 3-(2-hydroxyphenyl)-5-(aryl)-pyrazoline series was investigated for whole-cell efflux-pump inhibitory activity against Mycobacterium smegmatis and Mycobacterium abscessus. Machine learning and molecular dynamics were performed to construct a MmpL4/5 complex embedded in a lipid bilayer to identify the putative binding site and to predict ligand-protein binding energetics. Furthermore, the identified HIT compound was investigated in synergistic assay with bedaquiline. Results Compound Il, 2-(5-(4-fluorophenyl)-4,5-dihydro-1H-pyrazol-3-yl)phenol, was identified as the most potent efflux pump inhibitor against M. smegmatis in whole-cell efflux-pump investigation. Followed HIT Il employed against M. abscessus for efflux-pump inhibition investigations and notable whole-cell efflux-pump inhibitory profile has been observed. The theoretical investigations predicted compound Il to be selective towards MmpL4, with significant hydrogen bonding and π-π stacking interactions effectively blocking a critical Asp-Tyr dyad interaction network necessary for proton translocation. Compound Il with bedaquiline highlighted an additive profile against the M. abscessus pathogen. Conclusions MD simulations and whole-cell assays are indicating potential development of compound Il as an adjunct to the existing therapeutic regimen against mycobacterial infections.